Recent Progress in the Beneficiation of Iron-Manganese Ores: An Overview - Top, Soner (Pleiades Publishing Ltd, 2025)
Iron-manganese (Fe-Mn) ores are essential for steelmaking, ferroalloy production, and emerging energy technologies, yet their beneficiation is challenging due to the close association of Fe and Mn oxides and their overlapping physicochemical properties. This review assesses key processing strategies, including gravity separation, magnetic methods, flotation, reduction roasting, and selective reductive leaching. Physical beneficiation offers limited upgrades, being constrained by mineral liberation and ore texture. Reduction roasting with carbonaceous or hydrogen reductants exploits the different reduction stabilities of Fe and Mn oxides, creating magnetic contrasts for effective separation. Hydrometallurgical techniques based on reductive leaching also show strong potential, particularly with biomass-derived or organic reductants, achieving manganese recoveries often above 90-99%. A central focus is the use of Ellingham and Eh-pH diagrams as predictive tools for selective separation. Ellingham diagrams outline the thermodynamic stabilities of Fe and Mn oxides, guiding roasting design, while Eh-pH diagrams describe dissolution behavior under varying acidity and redox conditions, enabling leaching optimization. Integrating these frameworks with experimental evidence demonstrates how thermodynamic and electrochemical principles can improve process selectivity. No single technique universally addresses Fe-Mn beneficiation challenges; instead, hybrid flowsheets combining physical, thermal, and hydrometallurgical routes tailored to ore characteristics are most effective. Future research should prioritize low-carbon and sustainable approaches such as hydrogen roasting, bio-reductant leaching, and zero-waste systems. This review thus provides both a synthesis of current advances and a roadmap for sustainable Fe and Mn resource recovery.
Keywords: IRON; Mineral Processing; Leaching; Manganese; Separation